Writing on art of/for/from the Mindanao-Sulu Region a preliminary assessment - Canta, Marilyn R. (2004)
The writing on art of/for/from the regions and, more specifically, the Mindanao-Sulu region, may well reveal a landscape as exciting as the various geographical terrains that form it. A preliminary (read, tentative) assessment of this corpus of works within the last century reveals various observations indicative of both prevailing and changing attitudes towards regional art. This discussion therefore has several concerns: 1) to review "what has been done so far" on the region; 2) to identify approaches informing this writing; 3) to examine the authorship of these works; and 4) to point out fissures in this writing which may guide others towards future projects. In addition, the paper will be accompanied by a seminal bibliography of art writing in the region concerned.